The Effects of Rusip on the Amount of Lactic Acid Bacteria in Gastrointestinal Tract - Wiwin Efrizal; Hendro Wahyono; Andrew Johan (Faculty of Medicine, Diponegoro University, 2016)
Background : Rusip consumption can change the microbial composition of the digestive system. Microbial changes due to rusip consumption that is measured by lactic acid bacteria count has not been conducted.Objective : The purpose of the study was to analyze the effect of rusip consumption to the number of lactic acid bacteria in the gastrointestinal tract.Methods : Experimental study with post test only control group design using twelve Rattus novergicus Sprague dawley strains aged 2-2.5 months which were divided into 2 groups. Rats adapted for a week, then they were given rusip 5.1 mg/g body weight for 14 days. Cecal content were taken on the 22th day to be analysed for the lactic acid bacteria count.Results : The number of lactic acid bacteria (LAB) in the group given rusip was lower compared to the control group, but not significantly different (p=0.180). Weight gain was greater in the treatment group compared to the control group. The given group tends to have more weight in cecal content and lower pH compared to the control group.Conclusion : Rusip consumption does not increase the number of lactic acid bacteria in gastrointestinal tract.